Corrosion in airframes - Petrović, Zoran C. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The introductory chapter provides a brief reference to the issue of corrosion and corrosion damage to aircraft structures. Depending on the nature and dimensions of this nonuniformity, three different categories of corrosion are defined: uniform, selective and localized corrosion. The following chapters present the forms of corrosion that can occur in three defined categories of corrosion. Conditions that cause certain types of corrosion in various corrosive environments are discussed. Examples of corrosion processes are listed and mechanisms of these processes are briefly described. And, as a conclusion, the last chapter presents the summary of investigations of corrosion and corrosion damage to aircraft structures. Introduction Probably the best and broadest definition of corrosion says that corrosion is the degradation of mechanical properties of materials in the interaction with the environment. Corrosion in aeronautical structures must be considered as a significant problem, because it directly affects both the security and the economy-logistics. In view of the variety of materials, environments and mechanical stresses, aviation is one of the areas where the widest range of types of corrosion can be found. Depending on the nature and the dimensions of this non-uniformity, three different categories of corrosion can be experienced: Uniform corrosion, Selective corrosion and Localized corrosion. Uniform corrosion Although this is a very common mechanism in many corroded systems, it is not so often observed on airframes because the chosen aeronautical materials are always less prone to it. Uniform corrosion is common for non-stainless steel and iron where it can be easily recognized by red rust. Easily detectable and forecasted uniform corrosion cannot be considered a very dangerous form of corrosion. Selective corosion This category includes all the phenomena depending on the presence of heterogeneities in a chemical composition. In this sense, we can also talk about this electrochemical attack as caused by an intrinsic heterogeneity of the material. On airframes, intergranular corrosion is a more often observed mechanism of this class because it is a characteristic of aluminium alloys, both Al-Cu (2xxx) and Al-Zn (7xxx) alloys, where the driving force for the electrochemical process is the difference in potential between the second phase (richer in copper – more noble, or richer in zinc – less noble) and aluminium. In this case, a corrosion profile follows the shape of grain boundaries, and must be considered very dangerous because, in spite of minimum material loss, mechanical properties fall dramatically down. Localized corrosion This is certainly the class where the widest number of corrosion mechanisms is observed. The common factor among the different forms of corrosion in the case of a localized attack is the presence of stable and clearly separate cathodic and anodic areas. In the case of local corrosion, dissolution of metals can be done in one place, a reduction in the second place, and the creation of corrosion products in the third; in this case, the corrosion products will not protect the metal from further corrosion. Pitting corrosion: Pitting corrosion is a dangerous attack which occurs on passive materials when the protective oxide layer breaks. It is often observed on stainless steel and aluminium alloys that spontaneously form a protective film. Crevice corrosion: During the exploitation of metal structures, including steel structures, there may be the appearance of localized corrosion, which means the intense destruction in crevices (gaps). Crevices in structures are inevitable; they occur at connections of different parts which may be the same or different metals. Passive metals (corrosion resistant alloys, Al-alloys) have the greatest sensitivity to signs of corrosion in gaps. Galvanic corrosion: Galvanic corrosion is the most evident form of localized attacks, where anodic and cathodic areas are clearly identified. Filiform corrosion: Filiform corrosion can be found under organic coatings such as paints, due to penetration of moisture through the coated surface under specific temperature (T≥30°C) and humidity conditions (Hr ≥ 85%). Stress Corrosion Cracking and Corrosion-Fatigue: Unfortunately, these two dangerous localized corrosion mechanisms are often observed on airframes. Both produce cracks, different in shape and pattern, whose growth is caused by the synergetic action of a moderate corrosive environment and a mechanical stress: a static load (lower than the material’s yield tensile stress) in the case of SCC, or a cyclic load in the case of corrosion-fatigue (lower than the material’s fatigue limit). Conclusion In view of the variety of materials, environments and mechanical stresses, aviation is one of the areas where the widest range of types of corrosion is observed. Because of the absence of uniform classification and nomenclature of corrosive processes, existing classifications are incomplete and inaccurate. The categorization of corrosive processes in this paper was done on the basis of the structural-electrochemical theory, according to which the driving force of an electrochemical corrosion process is the presence of heterogeneity on the metal surface. Depending on the nature and dimensions of this nonuniformity, three different categories of corrosion are defined: uniform, selective and localized corrosion. Constantly expanding knowledge about the problems of corrosion, based on previous experiences and multidisciplinary approach to the design, as well as the development of non-destructive methods of analysis are essential for successfully confronting the economic and security challenges of aging aircraft.